Translation and cross-cultural adaptation of the Brazilian Portuguese version of the Driving Anger Scale (DAS): long form and short form - Jessye Almeida Cantini (Trends in Psychiatry and Psychotherapy, 2015)
Introduction: Driving anger has attracted the attention of researchers in recent years because it may induce individuals to drive aggressively or adopt risk behaviors. The Driving Anger Scale (DAS) was designed to evaluate the propensity of drivers to become angry or aggressive while driving. This study describes the cross-cultural adaptation of a Brazilian version of the short form and the long form of the DAS. Methods: Translation and adaptation were made in four steps: two translations and two back-translations carried out by independent evaluators; the development of a brief version by four bilingual experts in mental health and driving behaviors; a subsequent experimental application; and, finally, an investigation of operational equivalence. Results: Final Brazilian versions of the short form and of the long form of the DAS were made and are presented. Conclusions: This important instrument, which assesses driving anger and aggressive behaviors, is now available to evaluate the driving behaviors of the Brazilian population, which facilitates research in this field.